Analisis Beban Kerja Mental Operator Produksi Terhadap Produktivitas PT SWA I Dengan Metode DRAWS - Yoggi Aldi Trisnanto; Aloysius Tommy Hendrawan; Halwa Annisa Khoiri (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2024)
PT SWA I is a manufacturing company operating in the textile industry. There are 3 production process departments, namely Pre Treatment, Dyeing, and Finishing. The company has a production target of 300,000 yards per day, which will be exported to various countries as well as the local market. The high level of work pressure is often experienced by operators due to the demanding production targets and the requirement to meet the company's quality standards to ensure optimal productivity. Therefore, workload is a crucial aspect that needs to be considered. This study utilizes the Defence Research Agency Workload Scale (DRAWS) method to measure the workload. The DRAWS method consists of 4 indicator categories: Input Demand (ID), Central Demand (CD), Output Demand (OD), and Time Pressure (TP). Based on the DRAWS method, the total workload results for the Pre Treatment, Dyeing, and Finishing process departments are 75.06% (overload), 75.55% (overload), and 68.56% (overload), respectively, with the most dominant indicators being Output Demand, Central Demand, and Time Pressure. The processing and analysis of data show that the operator's workload is not optimal, especially in categories related to physical tasks, information interpretation, and time pressure. To improve and optimize the production process, it is suggested to enhance teamwork, improve information sheets, and optimize the system during the operator's working hours. This will result in better and more efficient production processes.